2015
DOI: 10.1007/s00521-015-1965-1
|View full text |Cite
|
Sign up to set email alerts
|

Learning node labels with multi-category Hopfield networks

Abstract: In several real-world node-label prediction problems on graphs, in fields ranging from computational biology to World-Wide-Web analysis, nodes can be partitioned into categories different from the classes to be predicted, on the basis of their characteristics or their common properties. Such partitions may provide further information about node classification that classical machine learning algorithms do not take into account. We introduce a novel family of parametric Hopfield networks (m-Category Hopfield Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…previous results obtained with inductive methods (Cesa-Bianchi et al, 2012), but the hierarchical correction of the predictions (Mostafavi and Morris, 2009;Cesa-Bianchi et al, 2012;Cozzetto et al, 2013;Robinson et al, 2015), and the multi-species setting of the classification problem (Wong et al, 2012;Mesiti et al, 2014) could further improve the performances of the proposed method, as shown by our recent results obtained with multi-category Hopfield networks, a variant of COSNet well-suited to multi-species protein function prediction problems (Frasca et al, 2015).…”
Section: Discussionmentioning
confidence: 55%
“…previous results obtained with inductive methods (Cesa-Bianchi et al, 2012), but the hierarchical correction of the predictions (Mostafavi and Morris, 2009;Cesa-Bianchi et al, 2012;Cozzetto et al, 2013;Robinson et al, 2015), and the multi-species setting of the classification problem (Wong et al, 2012;Mesiti et al, 2014) could further improve the performances of the proposed method, as shown by our recent results obtained with multi-category Hopfield networks, a variant of COSNet well-suited to multi-species protein function prediction problems (Frasca et al, 2015).…”
Section: Discussionmentioning
confidence: 55%
“…That is, before applying any algorithm to learn negative examples, it is of paramount importance studying which ‘protein representation’ is more informative for the problem itself. In this context, most information sources about the relationships between proteins are naturally represented through protein networks, where each node represents a protein and an edge the relationship between two proteins [13]; additionally, most approaches proposed for AFP are network-based [1420]. Thus, the purpose here is twofold: extracting meaningful protein features from protein networks, and assessing their ability to improve the identification of good negative examples.…”
Section: Introductionmentioning
confidence: 99%
“…for every task c k . Following the approach proposed in [16], a set of membership functions can be defined, extending the crisp memberships introduced above:…”
Section: Multitask Hopfield Networkmentioning
confidence: 99%